Answer :
Answer:
[tex]y=\frac{3}{2} x+6[/tex]
Step-by-step explanation:
We are given the following equation and we are supposed to solve y in terms of x. It simpler terms, it means that we have to make y the subject of the equation while x being used in it as it is:
[tex]\frac{2}{3} y-4=x[/tex]
Taking the constant 4 to the side where x is to get:
[tex]\frac{2}{3} y=x+4[/tex]
Multiplying the denominator 3 to the other side of the equation to get:
[tex]2y=3x+12[/tex]
Isolating y to make it the subject:
[tex]y=\frac{3}{2} x+\frac{12}{2}\\ \\y=\frac{3}{2} x+6[/tex]